Fermentation of high-salt liquid–state soy sauce without any additives by inoculation of lactic acid bacteria and yeast. (October 2020) - Liu, Rui; Gao, Guohuan; Bai, Yuwei; Hou, Lihua
Food additives are artificial or natural substances that are added to food to improve the color, aroma, taste, and other qualities, and to meet processing requirements. For the concern of food health and safety, brewed soy sauce without additives has attracted consumers' attention. Here, only four necessary raw materials including soybean, wheat, salt, and water were added. High-salt soy sauce fermentation was conducted for six months by sequential inoculation of lactic acid bacteria and yeast under different brine content (18%, 20%, and 22%). By analyzing the physicochemical indicators during moromi, three soy sauces (No. 1: 18% salt, inoculated with Tetragenococcus halophilus and Zygosaccharomyces rouxii, No. 5: 20% salt, inoculated with T. halophilus and Z. rouxii, No. 11: 22% salt, inoculated with T. halophilus and Candida versatilis ) were selected and sterilized to produce finished products for further comparative investigation. Results showed that the flavor components of these three soy sauces were richer in variety than the commercial soy sauces and No. 11 soy sauce was detected to have the largest total amount of organic acids. Plate count agar analysis revealed that the free amino acid differences of soy sauces were distinct, among which the No. 11 soy sauce had the highest glutamate content of 19.64 g L −1 . Besides, it was found that the shelf life of these three soy sauces could reach two years at 4 ℃. This study suggests that the high-salt soy sauce made by rational application of lactic acid bacteria, yeast, and effective sterilization can have high quality and long shelf life without adding any additives.